The forms of abstraction: W.S. Graham and Bryan Wynter. Issue 2 (1st February 2021) - Wilkinson, John
ABSTRACT: This article explores ideas of abstraction developed in the visual art and poetry produced in the artistic centre of St Ives in Cornwall during the mid-twentieth century. The first part briefly explores the St Ives milieu, the second offers a detailed reading of W.S. Graham's poem WYNTER AND THE GRAMMARSOW in relation to the painting and other artwork of Graham's friend Bryan Wynter, while the third considers how the practices of both poet and painter eventuate in works which remain 'adrift stationary'.